Efeito de película de carbono tipo diamante nas propriedades mecânicas e de superfície da resina acrílica termopolimerizável - Silva, Pâmela Lopes Pedro da (2016)
Introduction: The acrylic resin is used in dentistry for making dentures, orthodontic appliances and myo-relaxants splints; however, it has some limitations, such as low strength and high surface roughness. The diamond-like carbon (DLC) is a metastable form of amorphous carbon that can improve the resistance of various materials when applied as a film. Objective: To evaluate the effect of the DLC film application on the mechanical properties and surface of the acrylic resin thermally activated by power microwave (RAAT) (Vipi Wave). Materials and methods: Bodies of the test piece (flexural strength: 64 mm long x 10 mm wide x 3 mm; wear resistance: 4 mm diameter x 20 mm height, roughness: 10 mm diameter x 4 mm height) were obtained from the inclusion of replicas fiberglass flasks and polymerized according to the manufacturer. The deposition of films occurred by PECVD (Deposition Chemical Steam Assisted Plasma) with a thickness of 250 nm. They were divided into groups Gc (control) and Gt (treated) and underwent flexural strength test (n=18) in mechanical testing machine Instron (speed: 5 mm/min); wear resistance (n=18) biaxial Instron testing machine (load: 200 N, amplitude: 15 and frequency: 1,6 Hz) and analysis of the topography and surface roughness (Ra) by optical profilometry (n=18), with 5 objective measures of 20 X. the mean values were subjected to statistical tests of Mann-Whitney and t test to check the differences between the groups (p<0.05). Results: Gt showed higher roughness (0,108 ± 0,01 μm) than Gc (0,038 ± 0,01 μm), p<0,0001. There was no statistically significant difference (p=0,606) between Gt (103,3 MPa, IQ 97,67 ± 110,32) and Gc (105,3 MPa, IQ 98,95 ± 109,06) for resistance to flexion. There was no statistically significant difference between the groups in terms of straightness (Gt: 0,006 ± 0,0059 mm and Gc: 0,005 ± 0,0052 mm, p=0,774) and the depth of the indentations (Gt: 29,974 ± 8,69 μm and Gc : 28,169 ± 5,71 μm, p=0,610) after wear. Conclusion: The application of the DLC film on the surface of RAAT influenced the surface roughness having no effect on the flexural strength and wear.